Pembagian Harta Warisan Dalam Konsep Assitinajang dan Assiamaturuseng di Kabupaten Bone: The Distribution of Inheritance Property within the Concepts of Assitinajang and Assiamaturuseng in Bone Regency - Muftihaturrahma; Magono, Farhan Margono; Asni Zubair; Farid Al Hadana (QISTHOSIA : Jurnal Syariah dan Hukum, 2025)
This study examines Bugis inheritance distribution practices in Pattiro Riolo Village, Bone Regency, which are predominantly structured through assitinajang (propriety) and assiamaturuseng (consensual deliberation). The research addresses an urgent normative problem: clarifying the point of convergence and the limits of legitimacy between Bugis customary settlements and Islamic farā’iḍ rules, as local deliberative practices are often presumed either to be fully compliant with the Sharīʿa or entirely detached from it. Employing a socio-legal qualitative Design, primary data were collected through participant observation and semi-structured interviews with customary leaders, religious authorities, village officials, and heirs directly involved in inheritance settlement, complemented by a documentary review of family agreements. Data credibility was strengthened through source and method triangulation. The analysis combined descriptive qualitative procedures with a normative-evaluative framework that operationalizes Islamic inheritance principles as analytical benchmarks rather than mere doctrinal background. The findings reveal two dominant models: (1) post-mortem inheritance settlement through family deliberation, frequently reinforced by witnesses and written records; and (2) inter vivos transfers commonly framed locally as “inheritance distribution,” which are normatively closer to hibah (gifts) or waṣiyyah (bequests). From an Islamic legal perspective, assitinajang–assiamaturuseng is best interpreted as an iṣlāḥ/takhāruj-type mechanism and may be considered acceptable when specific conditions are met: heirs’ farā’iḍ entitlements are first identified as a baseline, any reallocation is grounded in genuine and informed consent, and no heir’s core rights, particularly those of vulnerable parties, are nullified. The study contributes a set of measurable normative indicators to assess whether the practice constitutes procedural adaptation, limited compromise, or a normative deviation from Islamic inheritance law, while also distinguishing social-legal legitimization (witnesses and written documentation) from strict Sharīʿa validity requirements.